C4d Deposition – An Independent Predictor of Graft Failure Following Liver Transplantation. (July 2018) - Iacob, Speranta; Cicinnati, Vito; Maschmeier, Miriam; Schmidt, Hartmut; Beckebaum, Susanne
Abstract : Introduction: Patient and graft survival after liver transplantation (LT) has strongly improved in the last decades. However, new data are emerging regarding causes of graft failure. Studies indicate that humoral response to both HLA and non-HLA antigens have a detrimental effect on allograft survival. Aim: To investigate clinical and immunological risk factors for graft failure at 5 years following LT. Methods: A total of 174 LT recipients were enrolled in the study. Patients underwent biopsy for histologic and C4d examinations. Assessment of sMICA, sMICB and sULBP2 was realized by enzyme linked immunosorbent assay. Screening for anti-HLA class I, class II or MICA antibodies was performed using Luminex technology. Graft failure was defined as histologically proven liver cirrhosis or allograft dysfunction requiring relisting for LT or leading to death. Cox proportional hazards regression model was used to identify predictors of graft failure after LT. Results: In the univariate analysis, the following factors were identified as risk factors for graft failure at 5 years: increasing donor age (p=0.0002), as well as the increasing recipient age (p=0.04), presence of disease recurrence after LT (p=0.03), presence of donor specific anti-HLA II antibodies >5000MFI (p=0.001), high serum levels of sMICA (p=0.01) and ULPB2 (p<0.0001), positive complement-dependent cytotoxic crossmatches at LT (p=0.0003), presence of positive C4d staining liver biopsies (p<0.0001). In multivariate analysis, C4d deposition (p<0.0001) and increased donor age (p=0.001) were independent predictors for graft failure at 5 years after LT. Conclusion: C4d deposition and advanced age of the donor (>66 years) correlated with allograft injury among LT patients.